Synthesis, characterization and anti-bacterial activity of newly synthesized coumarin and chalcone compounds consisting AZO (N=N) linkage - EKTA M. MESHRAM; BALIRAM N. BERAD; CHANDRASHEKHAR P. PANDHURNEKAR; HIMANI N. CHOPDE (International Journal of Pharma and Bio Sciences, 2018)
Coumarin nucleus is widely distributed in nature in plant kingdom and forms an important class of oxygen heterocycles. Derivatives of coumarins have been reported to posses different biological activities. Some of the well known anti-biotics namely Novobiocin, Coumaromycin and Chartesium are coumarin analogues. Keeping this view, the present study presents the synthesis of some novel derivatives of coumarin i.e. 3-(3-(aryl)acryloyl)-4-((4-nitrophenyl)diazenyl)-2H-chromen-2-one (2a-2e). Compounds (2a-2e) were synthesized from various aromatic aldehydes and 3-acetyl-4-((4-nitrophenyl)diazenyl)-2H-chromen-2-one (1) in the presence of sodium hydroxide and ethyl alcohol. 3-Acetyl-4-((4-nitrophenyl)diazenyl)-2H-chromen-2-one (1) was synthesized from 3-acetyl-2H-chromen-2-one and p-nitro amine in presence of NaNO2, HCl, Na2CO3 and NaOH at 0-5 oC. Different analytical techniques such as elemental analysis, IR spectra, 1H-NMR spectra and mass spectra were used to elucidate the structures of all the newly synthesized compounds. The anti-bacterial activity of the newly synthesized coumarin and chalcone compounds having azo linkage were evaluated against different bacterial stains such as S. aureus (gram-positive), B. subtilis (gram-positive), P. vulgaris (gram-negative) and E. coli (gram-negative). The anti-fungal activity of the newly synthesized coumarin and chalcone compounds were evaluated against different fungi stains such as C. albicans and A. niger. Compounds 2b against S. aureus (gram-positive), compound 2a against B. subtilis (gram-positive), compound 2d against P. vulgaries (gram-negative) and compound 2c against E. coli (gram-negative) have shown better anti-bacterial activity as compared to ciprofloxacin as a standard drug. Compound 2c have shown comparable activity against A. niger fungal stains as compared to flucanazole as standard drug. Some of the newly synthesized compounds shown promising bioactivity against different stains in the present study.